SYSTEMATIC LITERATURE REVIEW: PSYCHOLOGICAL CONCEPTS OF LEARNING IN HANDLING SPEAKING DELAY IN EARLY CHILDREN - Faruq, Nureyzwan Sabani, Agus Sukarno, Eny Purwandari (Universitas Muhammadiyah Surakarta, 2022)
Language learning for early childhood is directed at the ability to communicate, both orally and in writing. However, in reality there are still early childhood who have speech delays. The purpose of this review article is to review various journal articles regarding the handling of speech delay in early childhood. The method used is a literature review method with reference sources obtained from the Publish or Perish 7 program and Google Scholar. The criteria for articles used as references are journals published during 2015-2021 and full text can be accessed. The results of the selected article review stated that the teacher's efforts in handling speech delays in early childhood were the teacher doing classroom management, applying modeling methods, correcting word errors, inviting children to tell stories and using body movements, and selecting appropriate and interactive learning methods. Parents' efforts in handling speech delays in children are by increasing parents' knowledge about the concept of speech delay and having good storytelling skills, parents must know 10 signs of a child experiencing speech delay. Handling speech delay in children requires collaboration between schools, parents and the environment to help improve communication between children and their environment.